From Sudoscan to bedside: theory, modalities, and application of electrochemical skin conductance in medical diagnostics - Vittrant, Benjamin; Ayoub, Hanna; Brunswick, Philippe (Frontiers in Neuroanatomy, 2024)
The human body has two main types of sweat glands: apocrine and eccrine. Eccrine glands are widely distributed across the skin, including areas with hair. While the eccrine glands on palms and soles help improve grip, those on the rest of the body primarily aid in thermoregulation. Sudomotor function, which controls sweating, is regulated by the sympathetic division of the autonomic nervous system through cholinergic and adrenergic pathways. The activation of eccrine glands involves intricate processes, including neurotransmitter binding, ion channel modulation, and voltage generation. Sudoscan technology utilizes electrochemical skin conductance (ESC) to non-invasively measure sudomotor function. This method, which has been standardized for accuracy, has established normative benchmarks and has proven reliable across diverse populations. Sudoscan’s diagnostic performance is comparable to invasive methods such as intraepidermal nerve fiber density testing, making it a valuable tool for diagnosing small fiber neuropathy. Moreover, it has been shown to correlate with corneal nerve fiber length, providing insights into various neuropathic conditions. Compared to traditional sudomotor function tests, Sudoscan proves superior in terms of its accessibility, simplicity, and reliability, with the potential to replace or complement existing diagnostic methods. It is important to differentiate ESC, as measured by Sudoscan, from other skin conductance measures, such as galvanic skin response (GSR) or electrodermal activity (EDA). Although these methods share a common physiological principle, ESC is specifically designed for diagnosing sudomotor function, unlike GSR/EDA, which is typically used for continuous monitoring. Sudoscan’s success has led to its integration into consumer health devices, such as the BodyScan from Withings, showcasing its versatility beyond clinical settings. Future research may explore ESC applications in diverse medical fields, leveraging real-world data from integrated consumer devices. Collaborative efforts between researchers and engineers promise to offer new insights into sudomotor function and its implications for broader health monitoring. This study provides a comprehensive overview of ESC, including topics such as eccrine gland physiology, sudomotor function, Sudoscan technology, normative benchmarks, diagnostic comparisons, and potential future applications.